Rapid detection of Phytophthora cinnamomi based on a new target gene Pcinn13739 - Chen, Zhenpeng; Jiao, Binbin; Zhou, Jing; He, Haibin; Dai, Tingting (Frontiers in Cellular and Infection Microbiology, 2022)
Phytophthora cinnamomi causes crown and root wilting in more than 5000 plant species and represents a significant threat to the health of natural ecosystems and horticultural crops. The early and accurate detection of P. cinnamomi is a fundamental step in disease prevention and appropriate management. In this study, based on public genomic sequence data and bioinformatic analysis of several Phytophthora, Phytopythium, and Pythium species, we have identified a new target gene, Pcinn13739; this allowed us to establish a Recombinase Polymerase Amplification-Lateral Flow Dipstick (RPA-LFD) assay for the detection of P. cinnamomi. Pcinn13739-RPA-LFD assay was highly specific to P. cinnamomi. Test results for twelve isolates of P. cinnamomi were positive, but negative for 50 isolates of 25 kinds of Phytophthora species, 13 isolates of 10 kinds of Phytopythium and Pythium species, 32 isolates of 26 kinds of fungi species, 11 isolates of 2 kinds of Bursaphelenchus species. By detecting as little as 10 pg.µL−1 of genomic DNA from P. cinnamomi in a 50 µL reaction, the RPA-LFD assay was 100 times more sensitive than conventional PCR assays. By using RPA-LFD assay, P. cinnamomi was also detected on artificially inoculated fruit from Malus pumila, the leaves of Rhododendron pulchrum, the roots of sterile Lupinus polyphyllus and the artificially inoculated soil. Results in this study indicated that this sensitive, specific, and rapid RPA-LFD assay has potentially significant applications to diagnosing P. cinnamomi, especially under time- and resource-limited conditions.